Risk perception and participation intent in China’s domestic tourism sector / Li Jingyi - Li , Jingyi (2023)
Travel intention can be described as a customer's perceived likelihood of engaging in actions related to a tourism service, such as taking a trip. In the context of travel and tourism, intention to travel is studied as part of trip planning behaviour, which involves complex and dynamic decision-making processes with multiple interconnected determinants. The nature of tourism makes it susceptible to various risks, especially pandemics that can seriously undermine tourism. Tourists' perception of risk affects their travel intentions. With the spread of COVID-19, tourists are paying greater attention to the risks associated with travel, which may prevent them from traveling abroad. Due to the restricted measures on international travel worldwide, increasingly tourists prefer to choose safer and more convenient ways to travel for leisure purposed. Governments have started to implement strategies for attracting people to travel domestically. This study aims to understand tourists' travel intentions during the COVID-19 pandemic using the Theory of Planned Behaviour (TPB) and the Tripartite model of risk perception. An online survey was conducted in China during the pandemic that generated 400 usable responses. Using structural equation modelling, eight hypotheses were developed to evaluate the objectives of the study. The key outcomes of this research are: multidimensional risk perception has a significant influence on attitude and subjective norm. However, multidimensional risk perception did not influence perceived behavioural control, as Chinese people's perceived capability of engaging in domestic travel is not based on perceived risk. The results also show that multidimensional risk perception is positively associated with the intention to engage in domestic tourism. That is, the perception of the likelihood of a threat as a driving factor positively change individual’s behaviour. Moreover, travel intention is positively and significantly correlated with attitude, subjective norm, and perceived behavioural control. Attitude and subjective norm are significant mediators in the relationship between multidimensional risk perception and travel intention. However, perceived behavioural control only mediates the relationship between experiential risk perception and travel intention but has a weak effect. Lastly, perceived behavioural control had a moderating effect on the relationship between attitude and travel intention and the relationship between subjective norm and travel intention, meaning that the predictive power of attitude and subjective norm tends to increase with perceived behavioural control. The novelty of this research lies in the verification of the extended model of TPB with multidimensional risk perception, which has helped deepen our understanding of the TPB model. The study offers both theoretical and empirical contribution to travel behaviour intention research during the COVID-19 pandemic. Theoretically, the study applies the extended TPB model with multiple risk perceptions to fill the gaps found in the tourism risk perception literature. Practically, the study provides valuable insights for the Chinese tourism industry, which has been heavily damaged by the COVID-19 pandemic and can help tourism practitioners develop effective strategies to encourage domestic tourism to support the industry.